Addressing Gaps in Educational Evaluation: A Comprehensive Meta-Analysis - Arianda, Yoga Dwi; Triana, Dinny Devi; Madani, Faisal (Universitas Pendidikan Ganesha, 2024)
Educational evaluation plays a crucial role in ensuring the effectiveness of the learning process. However, various studies indicate gaps in the implementation of effective evaluation methods, such as the lack of a holistic approach and limited valid and reliable instruments. These gaps have the potential to undermine the quality of assessments of students' abilities. This article aims to explore the gaps in educational evaluation through a meta-analysis of several related studies. This study uses a meta-analysis design with a qualitative approach. Data for the study were obtained by identifying relevant research articles, selected based on the following criteria: publication in indexed journals, the main topic related to the development or evaluation of educational instruments, and the context of formal education. Primary data were derived from five key studies, which were analyzed in depth. The analysis process involved data categorization, thematic analysis, data interpretation, and result verification. The findings indicate that the development and validation of evaluation instruments based on innovative design and approaches are crucial in bridging the existing gaps. The development of more holistic evaluation methods, encompassing cognitive, affective, and psychomotor aspects, can provide a more comprehensive picture of students' abilities. Additionally, for educational policymakers, the findings highlight the importance of regulations that encourage comprehensive validation of evaluation instruments to support more meaningful teaching. The conclusion of this study is that the development of more effective and holistic evaluation instruments, supported by policies that encourage comprehensive validation, can significantly enhance the quality of educational evaluation.